2019
DOI: 10.1104/pp.19.00700
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Traits Contribute to Salinity Tolerance of Wild Tomato Seedlings from the Galapagos Islands

Abstract: Traits of modern crops have been heavily selected in agriculture, leaving commercial lines often more susceptible to harsh conditions compared with their wild relatives. Understanding the mechanisms of stress tolerance in wild relatives can enhance crop performance under stress conditions such as high salinity. In this study, we investigated salinity tolerance of two species of wild tomato endemic to the Galapagos Islands, Solanum cheesmaniae and Solanum galapagense. Since these tomatoes grow well despite bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 57 publications
1
38
0
3
Order By: Relevance
“…Tomato ( Solanum lycopersicum ) is one of the most consumed fruit and vegetable crops in the world (Zhu et al ., 2018). The wild ancestor of tomato is adapted to highly saline coastal habitats, while cultivated varieties have lost salt tolerance during domestication for larger fruit (Pailles et al ., 2020). By using a genome‐wide association approach, we recently identified genetic variations in the Na + –K + transporter SlHAK20 responsible for the variations in root Na + /K + ratio and the loss of salt tolerance during tomato domestication (Wang et al ., 2020).…”
Section: Figurementioning
confidence: 99%
“…Tomato ( Solanum lycopersicum ) is one of the most consumed fruit and vegetable crops in the world (Zhu et al ., 2018). The wild ancestor of tomato is adapted to highly saline coastal habitats, while cultivated varieties have lost salt tolerance during domestication for larger fruit (Pailles et al ., 2020). By using a genome‐wide association approach, we recently identified genetic variations in the Na + –K + transporter SlHAK20 responsible for the variations in root Na + /K + ratio and the loss of salt tolerance during tomato domestication (Wang et al ., 2020).…”
Section: Figurementioning
confidence: 99%
“…Landraces, as well as ancient and wild varieties are valuable resources for breeding programs [ 58 , 59 , 60 , 61 , 62 ]. For example, wild relatives from the Galapagos Islands ( S. cheesmaniae (L. Riley) Fosberg and S. galapagense S.C. Darwin and Peralta) are endemic species adapted to the highly saline coastal areas and a recent screening of 67 accessions revealed that different traits are involved in the high tolerance to salinity [ 62 ].…”
Section: Tomato As Model To Study the Response To Salt Stressmentioning
confidence: 99%
“…Landraces, as well as ancient and wild varieties are valuable resources for breeding programs [ 58 , 59 , 60 , 61 , 62 ]. For example, wild relatives from the Galapagos Islands ( S. cheesmaniae (L. Riley) Fosberg and S. galapagense S.C. Darwin and Peralta) are endemic species adapted to the highly saline coastal areas and a recent screening of 67 accessions revealed that different traits are involved in the high tolerance to salinity [ 62 ]. Tomato landraces from Southern Italy showed higher tolerance to drought via the constitutive increased activities of catalase, ascorbate peroxidase and glucose-6-phosphate dehydrogenase [ 63 ], while in the wild halophyte ( S. chilense ) exposed to NaCl, an increase in ethylene biosynthesis, accompanied by the upregulation of the 1-aminocyclopropane-1-carboxylic acid synthase ( ACCS2 ) gene, was correlated with a high tolerance to salinity [ 64 ].…”
Section: Tomato As Model To Study the Response To Salt Stressmentioning
confidence: 99%
“…The majority of tomato cultivars have the genetic potential to tolerate mild to medium salt stress [ 17 ]. Every plant growth and development stage (seed germination, vegetative and reproductive growth) demonstrate sensitivity to salinity stress, leading to decreased crop performance and yield [ 18 , 19 ]. However, in many crops, studies have revealed that salinity tolerance at the early growth stages is of more importance than at the later plant stages [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%